The Impact of Whey Protein and/or Omega-3 Fatty Acid Supplementation on Body Composition, Energy Expenditure and Metabolic Health in Postmenopausal Women (SHAPE Study). (7th June 2021) - Hawley, Aubree; Tacinelli, Angela; Walker, Sam; Liang, Xinya; Baum, Jamie
Abstract: Objectives: Age-related deleterious shifts in body composition can lead to sarcopenia, which is the age-related loss of muscle mass, strength, and function. Furthermore, declines in endogenous estrogen production during the menopausal transition are associated with muscle mass loss and increased central adiposity, putting postmenopausal women at increased risk for negative health outcomes such as cardiovascular disease and type-2 diabetes mellitus. The objective of this study was to determine the effect of protein and/or omega-3 fatty acid (O3FA) supplementation on metabolic health in postmenopausal women. Methods: Thirty-nine postmenopausal women (age: 61.3 ± 8.7 years; BMI: 27.6 ± 6.6 kg/m 2 ) were randomly allocated to one of 5 groups: 1) control (CON; no intervention free-living; n = 6), 2) whey protein isolate (PRO; 25 g/d; n = 7), 3) O3FA (DHA/EPA; 4.3 g/d; n = 10), 4) PRO + placebo soybean oil (PRO + PLA; 4.1 g/d; n = 7), or 5) PRO + O3FA (n = 9). Energy expenditure via indirect calorimetry, dietary intake via 3-day weighed dietary records, hand grip strength (HGS), and metabolic health were assessed at 0, 4, 8, 12, and 16 weeks. Body composition was measured via dual x-ray absorptiometry at 0 and 16 weeks. Metabolic health was assessed using waist-to-hip ratio and biomarkers such as plasma glucose, insulin, free fatty acids, and cholesterol. Results: There was not an effect of treatment effect on anthropometrics, body composition, HGS, or resting energy expenditure. However, a decrease in android fat % was observed in PRO compared to baseline (P < 0.05) in the absence of anthropometric change (BMI, weight, waist, hip). A significant group by time effect was observed on resting fat oxidation (P < 0.05); O3FAs (+34.6%; P < 0.05) and PRO + O3FAs (+55.6%; P < 0.05) significantly increased and PRO decreased (−37.8%; P < 0.05) from baseline to 16 weeks. There was a significant (P < 0.05) decrease in cholesterol in all groups compared to CON. Conclusions: Although not significant, the data suggests individual and combined supplementation of protein and O3FA have the potential to improve body composition and substrate oxidation in postmenopausal women. NCT0303041 Funding Sources: Arkansas Biosciences Institute